Raising Student Health Via Who’s 6-Step Hygiene During KKN Program in Payaraman District South Sumatra - Ghiffari, Ahmad; Asmalia, Resy; Ihsan, Muhammad; Wildan, Sahrul; Kurnia, Aisyah Fadhilah; Sandi, Louwen; Fatihah, Nabila Nurul; Andelina, Rizky; Nurfauza, Aqila Meisya Putri Mulya; Hidayat, Muhammad Wahyu; Dwitania, Tasya Julia (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2025)
ABSTRACT The 63rd KKN program at Universitas Muhammadiyah Palembang involved medical students in community service, focusing on raising awareness and practice of the WHO 6-step handwashing method to prevent infections and promote nutritional health. This study aimed to evaluate the effectiveness of community education on proper handwashing techniques among elementary students. The outreach program included preparation, implementation, and evaluation phases, with educational materials, school visits, counseling, demonstrations, and hands-on practice. A total of 43 students SDN 6 participated, showing significant improvements in knowledge and behavior. At SDN 1, MIN 1 Payaraman and KKN Posko, educational activities and WHO handwashing initiatives were implemented; however, no pre-tests or post-tests were administered. The six-step handwashing education and the automatic hand soap dispenser effectively enhanced students' knowledge and enthusiasm for cleanliness through handwashing at UPT SPD N 06. To maintain this program, the school should implement frequent educational sessions and guarantee the provision of adequate clean water inside the school premises. Keywords: 6-Step Handwashing WHO; Automatic Foam Soap Dispenser, Behavior Change, Elementary School Students, KKN Program